A Liderança de mulheres no desenvolvimento da comunidade Divino Espirito Santo Vicinal 15 - SANTOS, Maria Sandra do Nascimento (2018)
This article addresses the history of a rural community that has always been under the leadership of women; At the beginning of this article there is a general overview about the history of the opening of the Transamazonica, followed by stories of women protagonists for the social, cultural and intellectual development of the Divino Espírito Santo community located in Vicinal 15, based on reports of women who were invited to participate in a research with semi-structured interviews, in which they would have to tell how their trajectory to the present day was in the search of improvements for this community.